Perkembangan Morfologi Gresik Kota Bandar dengan Pendekatan Analisa Diakronik - Gratia Ananda Sinaga; Karina Pradinie Tucunan; Putu Rudy Satiawan; Dian Rahmawati (Universitas Diponegoro, Indonesia, 2021)
Gresik Regency as a Bandar has been known since the Majapahit Empire because of its strategic location and high trading activities that have made Gresik a Bandar City. The existence of Bandar Gresik is one of the reasons for the diversity of history and culture contained in it because of the acculturation of the immigrant culture caused by the Bandar itself. Bandar is one of the triggers for community and economic development which is increasingly seen in the morphology of the City of Gresik Regency. The existence of various historical relics, both tangible and intangible, describes historical events that have occurred in Gresik Regency in the past and city developments that have occurred to the present. This historical event of Gresik Regency can then become its own identity and uniqueness for Gresik Regency. Therefore, it is necessary to conduct a study on the development of Gresik with the aim of seeing what the development of Gresik Regency looks like from year to year to find out the morphological form that existed at that time and how important it is for spatial regeneration in the future. This study uses a content analysis (CA) analysis approach and Diankronik analysis. The results of this study found 5 stages of the main period consisting of the Majapahit Empire, the Islamic Development Period, the Colonial Period, the Japanese Occupation Period, and the Early Independence Period. Based on the development period, they are grouped into four historical areas, namely the Bandar Gresik area, the Giri area, the Bandar Jaratan area and the Bawean area.